ANALISIS PENERAPAN SISTEM AKUNTANSI PENDIDIKAN PADA PENDIDIKAN ANAK USIA DINI AL FAHMY DESA NGIJO KARANGANYAR - Dewi Saptantinah Puji Astuti (Universitas Slamet Riyadi, 2014)
ABSTRACT The research was conducted in the non-profit oriented organization, namely the Al Fahmy Playgroup, arguing that playgroup education has been growing but the implementation is still a lot that has not been guided by the procedures and the resulting financial statements are not in accordance with accounting standards education. The purpose of this study is to provide an overview for managers in the field of education on the importance of the application of the accounting system of education in the context of the delivery of financial accountability. The study was descriptive data is the primary data, from interviews and secondary data derived from the documents and related references. From the research, it was concluded that playgroup education is still not understood the proper accounting standards for use, and there are still many weaknesses in the control intern, for example with the lack of segregation of duties functions in the playgroup, as well as documents and records are still sober, and incomplete. Keywords: accounting systems, accounting procedures, accounting standards education